Explanation:
1.
there are two given value for x so the value of y will change accordingly
for x = -1 ➡ y + 5 × -1 = 6 ➡ y = 11
and for x = 0 ➡ y + 5 × 0 = 6 ➡ y = 6
2.
for x = -3 ➡ 8×-3 -4y = -12 ➡ y = -3
for x=-1 ➡ 8×-1 -4y = -12 ➡ y = 1
3.
for x = -3 ➡ -3y = 2× -3 -9 ➡ y = 5
for x = 0 ➡ -3y = 2×0-9 ➡ y = 3
4.
for x = 1 ➡ 5×1 = -y + 6 ➡ y = 1
for x = 2 ➡ 5×2 = -y + 6 ➡ y = -4
5.
for x = -4 ➡ 6y = (-4)×(-3)+12 ➡ y = 4
for x = -2 ➡ 6y = (-2)×(-3)+12 ➡ y = 3
6.
for x = -2 ➡ -5y + 10×(-2) = 5➡ y = -5
for x = 0 ➡ -5y + 10×0 = 5➡ y = -1